2020
DOI: 10.1523/jneurosci.0969-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Nonionotropic Action of Endothelial NMDA Receptors on Blood–Brain Barrier Permeability via Rho/ROCK-Mediated Phosphorylation of Myosin

Abstract: Increase in blood-brain barrier (BBB) permeability is a crucial step in neuroinflammatory processes. We previously showed that N Methyl D Aspartate Receptor (NMDARs), expressed on cerebral endothelial cells forming the BBB, regulate immune cell infiltration across this barrier in the mouse. Here, we describe the mechanism responsible for the action of NMDARs on BBB permeabilization. We report that mouse CNS endothelial NMDARs display the regulatory GluN3A subunit. This composition confers to NMDARs' unconventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 43 publications
2
41
2
Order By: Relevance
“…levamisole, induced the retraction of endothelial cells [33]. Endothelial cell retraction and detachment are prototypical indicators of cytoskeletal reorganization and have been shown to accompany BBB dysfunction and increase cellular permeability [46,47]. We observed that treatment of BMECs with TNF-α and IFN-γ combined with inhibition of TNAP enzymatic activity disrupted the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…levamisole, induced the retraction of endothelial cells [33]. Endothelial cell retraction and detachment are prototypical indicators of cytoskeletal reorganization and have been shown to accompany BBB dysfunction and increase cellular permeability [46,47]. We observed that treatment of BMECs with TNF-α and IFN-γ combined with inhibition of TNAP enzymatic activity disrupted the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 83%
“…ROCK protein expression has been shown to play a role in regulating cytoskeletal proteins such as vimentin and actin by initiating F-actin contraction/retraction and cellular detachment [37,35,46]. Upstream of ROCK is the RhoA protein, one of many proteins that drives the activation of ROCK, and the Rho-ROCK pathway has been shown to play an important role in endothelial cell function Based on our cytoskeletal findings, we addressed whether the Rho/ROCK pathway was implicated in TNAP signaling.…”
Section: Discussionmentioning
confidence: 97%
“…In mouse experimental autoimmune encephalomyelitis (a model of multiple sclerosis), gene inactivation of cortactin reduced neuroinflammation and a lack of cortactin ameliorated leukocyte migration across the brain endothelium in vivo and in vitro. Mehra et al [6] also reported that activation of N-Methyl-d-Aspartate Receptors (NMDARs) in brain endothelial cells upregulates immune cell infiltration into brain by phosphorylating myosin light chain and subsequent cell shrinkage. Interestingly, endothelial and neuronal NMDARs differ in structure, function and pharmacology.…”
Section: Brain Endotheliummentioning
confidence: 99%
“…Previously, it was shown that post-TBI inflammatory responses are initiated by peripheral immune mediators that enter the CNS through the porous BBB. 7 Therefore, in trauma, inhibiting the expression of related immune mediators and repairing the integrity of the BBB can stabilize the brain microenvironment, reduce the pathological response, and improve the long-term disease prognosis. Accumulation of the misfolded proteins in the endoplasmic reticulum (ER), causing dysfunction of ER, is known as ER stress.…”
Section: Introductionmentioning
confidence: 99%